EXPLORING THE ROLE OF SELF-EFFICACY AND COPING STRATEGIES IN ENHANCING CAREER READINESS AMONG UNIVERSITY STUDENTS: A HUMAN RESOURCE MANAGEMENT PERSPECTIVE - Dinis Cahyaningrum; Isra Dewi Kuntary Ibrahim; Ni Wayan Adelia Mutiara Asri; Dhanny Safitri; Tifani Dame Hasani (Laboratorium Riset Ekonomi, 2026)
The transition from higher education to employment has become increasingly challenging due to rapid technological change, global competition, and evolving workforce demands. This study aims to explore the role of self-efficacy and coping strategies in enhancing career readiness among university students from a Human Resource Management (HRM) perspective. This study employed a qualitative descriptive approach using a literature review methodology. Relevant studies were collected from academic databases and analyzed thematically to identify patterns and relationships among self-efficacy, coping strategies, and career readiness. The findings reveal that self-efficacy is a key predictor of career readiness, influencing students’ confidence, career planning, decision-making, and employability perceptions. Adaptive coping strategies also contribute to resilience and psychological adaptability, enabling students to manage career-related stress and uncertainty more effectively. Furthermore, the literature indicates a strong relationship between self-efficacy and coping strategies, suggesting that both factors jointly support successful career transitions. From an HRM perspective, these psychological resources represent important components of human capital that enhance graduates’ employability and workforce readiness. The study concludes that strengthening self-efficacy and adaptive coping strategies can improve career readiness among university students. Therefore, universities should integrate psychological development into career preparation programs to better prepare graduates for dynamic labor market conditions.